Voter Beliefs and Strategic Voting in Two-Round Elections. (December 2021) - Plutowski, Luke; Weitz-Shapiro, Rebecca; Winters, Matthew S.
How widespread is strategic voting in two-round electoral systems, and which types of voters are most likely to engage in such behavior? While runoff elections are common in presidential systems around the world, research on strategic voting in these settings remains limited. This paper explores four different types of strategic behavior that are possible in two-round systems, including some types, such as "strong-to-weak" strategic voting, which are not possible in single-shot elections. We use a nationwide survey to assess the incidence and correlates of strategic voting in Brazil's 2018 presidential election, where thirteen candidates competed in the first round. We find evidence of "weak-to-strong" strategic voting at a similar rate to that documented in single-round elections in other countries. We find little evidence of other types of strategic voting. Furthermore, we show that voters' confidence in their predictions of the likely electoral outcome and their ideological preferences strongly predict strategic voting. These results point to the importance of accounting for voter beliefs and attitudes in addition to objective voter characteristics to explain strategic voting.